Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Let's solve the equation step-by-step: [tex]\(\sqrt{2n + 28} - 4\sqrt{n} = 0\)[/tex].
1. We start with the given equation:
[tex]\[ \sqrt{2n + 28} - 4\sqrt{n} = 0 \][/tex]
2. To isolate [tex]\(\sqrt{2n + 28}\)[/tex], let’s make [tex]\(\sqrt{2n + 28}\)[/tex] equal to [tex]\(4\sqrt{n}\)[/tex]:
[tex]\[ \sqrt{2n + 28} = 4\sqrt{n} \][/tex]
3. Now, we square both sides of the equation to remove the square roots:
[tex]\[ (\sqrt{2n + 28})^2 = (4\sqrt{n})^2 \][/tex]
Simplifying this, we get:
[tex]\[ 2n + 28 = 16n \][/tex]
4. We need to solve for [tex]\(n\)[/tex]. Let’s isolate [tex]\(n\)[/tex] on one side of the equation:
[tex]\[ 2n + 28 = 16n \][/tex]
Subtract [tex]\(2n\)[/tex] from both sides:
[tex]\[ 28 = 14n \][/tex]
5. Finally, divide both sides by 14:
[tex]\[ n = \frac{28}{14} \][/tex]
[tex]\[ n = 2 \][/tex]
So, the solution to the equation [tex]\(\sqrt{2n + 28} - 4\sqrt{n} = 0\)[/tex] is [tex]\( n = 2 \)[/tex]. Therefore, from the given options, [tex]\( n = 2 \)[/tex] is the correct answer.
1. We start with the given equation:
[tex]\[ \sqrt{2n + 28} - 4\sqrt{n} = 0 \][/tex]
2. To isolate [tex]\(\sqrt{2n + 28}\)[/tex], let’s make [tex]\(\sqrt{2n + 28}\)[/tex] equal to [tex]\(4\sqrt{n}\)[/tex]:
[tex]\[ \sqrt{2n + 28} = 4\sqrt{n} \][/tex]
3. Now, we square both sides of the equation to remove the square roots:
[tex]\[ (\sqrt{2n + 28})^2 = (4\sqrt{n})^2 \][/tex]
Simplifying this, we get:
[tex]\[ 2n + 28 = 16n \][/tex]
4. We need to solve for [tex]\(n\)[/tex]. Let’s isolate [tex]\(n\)[/tex] on one side of the equation:
[tex]\[ 2n + 28 = 16n \][/tex]
Subtract [tex]\(2n\)[/tex] from both sides:
[tex]\[ 28 = 14n \][/tex]
5. Finally, divide both sides by 14:
[tex]\[ n = \frac{28}{14} \][/tex]
[tex]\[ n = 2 \][/tex]
So, the solution to the equation [tex]\(\sqrt{2n + 28} - 4\sqrt{n} = 0\)[/tex] is [tex]\( n = 2 \)[/tex]. Therefore, from the given options, [tex]\( n = 2 \)[/tex] is the correct answer.
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.